Robert Ludlum's the Treadstone exile - Hood, Joshua; Ludlum, Robert, 1927-2001 (Hood, Joshua. Treadstone series, 2022)
Hood's fast-paced sequel to 2019's Robert Ludlum's The Treadstone Resurrection finds Adam Hayes, a former operative for Treadstone, a CIA unit that "turned him into a government-sanctioned assassin," in Ceuta, Spain, where he's feeling proud of himself for not having killed anyone in 152 days. He's left his wife and child behind in America and gone on the run after the U.S. government declared him persona non grata. In Ceuta, he becomes involved in a smuggling ring, and the no-kill record is soon broken. Meanwhile, Andre Cabot, the founder and CEO of a cybersecurity firm, is in financial difficulty, and decides to steal his way back into solvency. Hayes lands right in the middle of Cabot's plans and must be dealt with. Never mind cliched prose ("get the hell out of Dodge"), a surfeit of backstory, and voices in the heads of Hayes and other characters that yammer at them in italics. Few thriller fans will be able to resist as the author hauls them by their necks down many rough roads while Hayes mows down the opposition.